Model studies on groundwater efficiency as a low-grade energy source - V. R. Voloshin; K. V. Belov (Известия высших учебных заведений: Геология и разведка)
Background. New energy-saving technologies induce the implementation of alternative heat supply sources, including heat pump systems. One of their operational schemes utilizes low-grade heat from groundwater aquifers. The paper substantiates the selection of the most optimal operational scheme based on model calculations.   Aim. To conduct model calculations aimed at computing the feasibility of using groundwater aquifers as a low-grade heat energy source.   Materials and methods. The hydrodynamic processes and heat transfer within the aquifer were studied using the GERA/E1.0 computational code, designed for three-dimensional geofiltration and geomigration modeling.   Results. Several numerical models are developed for various operational schemes of groundwater aquifers. The most promising operational scheme was selected based on the calculations.   Conclusion. The feasibility of using groundwater aquifers as a low-grade heat energy source has been quantitatively assessed. The most optimal operational scheme has been selected.